Aplicaciones del Arteterapia en aula como medio de prevención para el desarrollo de la autoestima y el fomento de las relaciones sociales positivas: “Me siento vivo y convivo “ - Elena Rodríguez Fernández (Arteterapia)
“I feel alive and co live” project is the acting frame for working in the public education at a school in Madrid in which students coming from a foreign origin in their majority co live. Along three consecutive courses, “Arteterapia” has been introduced gradually with the agreement of the teachers’ department. The main aim has been to increase self esteem and improve social relationships by means of plastic arts, music and dancing, based on “Arteterapia” defining principles. In the first course of application, the project was implemented in first grades (children education). It was extended afterwards in the following teaching period to different levels of Primary Education in order to gather in the present course the whole student community. This is a project included within the institutional programme “To Co live is to Live” destined to help those centres that work towards the prevention of violence in the educative sphere. The project’s objectives are developed around artistic education, musical education and physical education with students of first grades and Primary Education. During the process, the teachers implied have received a series of training sessions in which craft classes of Arteterapia, Musicoterapia and Danzaterapia were included.